2021
DOI: 10.1186/s12913-020-06040-5
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of alternative testing regimes and settings to detect undiagnosed HIV in Australia

Abstract: Background The study aimed to estimate the comparative costs per positive diagnosis of previously undetected HIV in three testing regimes: conventional; parallel and point of care (POC) testing. The regimes are analysed in six testing settings in Australia where infection is concentrated but with low prevalence. Methods A cost model was developed to highlight the trade-offs between test and economic efficiency from a provider perspective. First, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…The efficacy of deliberately organized and advertised HIVST programs has previously been proved to yield positive results in youths [ 19 , 47 , 48 ]. Using trained kit distributers like Peer Educators in program implementation offered individual support and reduced clinical service demands and allowed clinicians to focus their expertise on complex case management [ 49 ]. Disconnecting testing from clinical facility settings and reducing interactions with health providers was predicted to diminish negative perceptions associated with HIV testing experiences [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of deliberately organized and advertised HIVST programs has previously been proved to yield positive results in youths [ 19 , 47 , 48 ]. Using trained kit distributers like Peer Educators in program implementation offered individual support and reduced clinical service demands and allowed clinicians to focus their expertise on complex case management [ 49 ]. Disconnecting testing from clinical facility settings and reducing interactions with health providers was predicted to diminish negative perceptions associated with HIV testing experiences [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Partnerships with PLHIV and those at risk are central to understanding how HIVST kits can be added to the existing suite of HIV testing modalities to facilitate testing uptake among those not testing or accessing other testing options. This peer-supported model also has health economic value, reducing clinical service demands and redirecting clinicians’ time and expertise to complex case management [ 24 ]. This study does, however, have some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…HIV self-testing (HIVST) provides convenience and privacy for the person testing [ 17 ], and offers additional opportunities to address identified barriers to testing [ 12 , 15 , 18 , 19 ]—especially when appropriately targeted to at-risk populations [ 20 ] and combined with peer-based support [ 21 ]. Mathematical modelling suggests that HIVST will increase access to and uptake of HIV testing if used to complement existing conventional and rapid testing practices [ 22 , 23 ], at very little cost [ 24 ]. A recent Australian randomized controlled trial demonstrated that the availability of HIVST for MSM doubled HIV testing frequency overall, and resulted in a fourfold increase in testing among non-recent HIV testers [ 25 ].…”
Section: Introductionmentioning
confidence: 99%